Synthesis of Cr2O3/C3N4 doped PVA polymer membranes for optoelectronic applications - Khulaif Alshammari; Alhulw H. Alshammari (Polymer Testing, 2024)
This study reports the synthesis and characterization of Cr₂O₃/g-C₃N₄ doped PVA nanocomposite membranes using a solution casting method for potential optoelectronic applications. The successful incorporation of Cr₂O₃ and g-C₃N₄ into the PVA matrix was confirmed through various analytical techniques, comprising FTIR, XRD, SEM, EDX, and XPS. The addition of Cr₂O₃/g-C₃N₄ resulted in enhanced thermal stability, as demonstrated by an increase in decomposition temperature by 25–38 °C. Optical analysis revealed a reduction in both direct and indirect band gaps, from 5.41 eV to 4.85 eV and 5.18 eV–4.65 eV, respectively, indicating modifications in the electronic structure of the composite. This enhancement in optical and thermal properties can be linked to the robust interfacial interactions between the nanofillers and the PVA matrix. The novelty of this research lies in the synergistic effect of Cr₂O₃ and g-C₃N₄, which not only improves the composite's stability and optical properties but also provides a pathway for the development of advanced materials with tunable electronic characteristics for optoelectronic devices. The results of this study contribute to the growing need for environmentally friendly, high-performance materials that can be utilized in a variety of implementations, such as sensors and flexible electronics, thereby having a positive impact on technology development and societal progress.